The first transcriptome and genetic linkage map for Asian arowana. (3rd January 2014) - Shen, X. Y.; Kwan, H. Y.; Thevasagayam, N. M.; Prakki, S. R. S.; Kuznetsova, I. S.; Ngoh, S. Y.; Lim, Z.; Feng, F.; Chang, A.; Orbán, L.
Abstract Asian arowana or dragonfish (Scleropages formosus) is an important fish species due to its unusual breeding biology and high economic value in the ornamental fish markets. In the present study, we aimed to (i) create the first transcriptome by Roche 454 pyrosequencing of Asian arowana brain and gonad samples; (ii) identify differentially expressed genes between the two sexes and develop microsatellite (SSR) markers; and (iii) construct a first‐generation SSR‐based genetic linkage map. A total of over 1.3 million reads were obtained from the brain and gonad of adult Asian arowana individuals through pyrosequencing. These reads were assembled into 16 242 contigs that were further grouped into 13 639 isogroups. BLASTX annotation identified a total of 8316 unique proteins from this data set. Many genes with sexually dimorphic expression levels and some putatively involved in sex development were identified. A total of 316 EST‐SSRs and 356 new genomic‐SSRs were developed by screening through the current transcriptome data set and SSR‐enriched genomic libraries. The first genetic linkage map of the species was constructed based on these markers. Linkage analysis allowed for mapping of 308 markers to 28 linkage groups (LGs), ranging in size from 14.9 to 160.6 cM. The potentially sex‐associated gene sox9 was mapped to LG4 on the consensus linkage map. Pairwise putative conserved syntenies between the Asian arowana, zebrafish, and three‐spined stickleback were also established. These resources will help the conservation of the species through better understanding of its phylogenetics, genomics and biology, and comparative genome analysis within the Osteoglossidae family.